Renoprotective and antihypertensive mechanism of action of Clinacanthus nutans bioactive polysaccharides by suppression of reactive oxygen species/ nuclear factor/ matrix metalloproteinase (ROS/NF-ΚB/MMP-9) and upregulation of endothelial nitric oxide synthase/nitric oxide (eNOS/NO) pathways - Chia, Tan Yong; Gan, Chee Yuen; Cheah, Pike See; Murugaiyah, Vikneswaran; Fatima, Tabinda; Haji, Esraa M.; Almutairy, Ali F.; Mohammed Alnasser, Sulaiman; Alswailmi, Farhan K.; Ahmad, Ashfaq (Springer Science and Business Media, 2025)
Clinacanthus nutans (C. nutans) Lindau, is classified as a top herb which are investigated for different biological activities like antioxidant, anti-inflammatory and vasodilatory effects. Hitherto, no dedicated study has been investigated on the role of C. nutans in L-NAME [N(ω)-nitro-L-arginine methyl ester] in-vivo rat model to explore its antihypertensive and renoprotective mechanism by modulating the ROS/NF-κB/MMP-9 pathways both globally in the plasma as well as locally in the kidney by using in-vitro expression study. Present study hypothesized that bioactive polysaccharides leaves of the alcoholic extract of C. nutans (CNBP) could improve the functions of the kidney by its antioxidant, anti-inflammatory, antihypertensive actions by suppression of ROS/NF-κB/MMP-9 and upregulation of eNOS/NO pathways in the plasma and kidney. Thirty male Sprague–Dawley (SD) rats (n = 6) were randomised into five groups namely: Control (C), L-NAME (L) administered in drinking water, L-NAME + 500 mg/kg of C. nutans bioactive polysaccharides (CNBP) (LCN500), L-NAME + 1000 mg/kg of CNBP (LCN1000) and L-NAME + 2000 mg/kg of CNBP (LCN2000) respectively. All treatments were continued for the period of 14 days and physiological data like water intake, urine output, body weight was collected on days 0, 7 and 14. Acute in-vivo study was performed after cannulation of the femoral and carotid arteries where renal cortical blood perfusion (RCBP) was measured along with pulse wave velocity (PWV). Plasma and renal malondialdehyde (MDA), tumour necrosis factor-α(TNF-α), interleukin-6 (IL-6), matrix metalloproteinase-9 (MMP-9), intercellular adhesion molecule-1 (ICAM-1), nitric oxide synthase-1 (NOS1) and superoxide dismutase (SOD) were measured. Histopathological studies were done on the kidney tissue at the termination of experiment. Administrations of L-NAME to L group for 14 days resulted in significantly reduced levels of SOD and NOS while significantly elevated levels of MDA, TNF-α, IL-6 and MMP-9 in both plasma and kidney tissue when compared to control group (C). Conversely, treatment of 500, 1000 and 2000 mg/kg of CNBP has significantly reversed the values when same was compared to normal control ( C) group. Administration of L-NAME to L group for 14 days caused significantly increased systolic blood pressure (SBP) and arterial stiffness by increasing the pulse wave velocity (PWV) along with reduced creatinine clearance and renal cortical blood perfusion (RCBP) when compared to C group. Nevertheless, treatment of 500, 1000 and 2000 mg/kg CNBP has significantly reduced the SBP and PWV and raised the creatine clearance and RCBP functions when compared to (L) group. This study devised with the novel findings of 14 days CNBP treatment has suppressed ROS/TNF-α/MMP-9 pathway in the plasma and kidney which is pathological pathway for the kidney injury and hypertension while upregulated eNOS/NO pathways in plasma and kidney which is renoprotective and antihypertensive pathway in L-NAME rat model of hypertension and kidney injury.